Analysis of Teachers Pedagogical Competence in Teaching English at The Second Grade of SMK NEGERI 4 GOWA - Titi Amalia; Ummi Khaerati Syam; Ardiana (English Language Teaching Methodology, 2023)
This research aims to determine the pedagogical ability of teachers in teaching English in grade II OF SMK NEGERI 4 GOWA. The subject of this study used the qualitative descriptive method. This study focused on the eleventh grade level of SMK Negeri 4 Gowa and the main subjects of this study were two English teachers of SMA NEGERI 4 GOWA. The data in this study were taken from observations and interviews. The form of checklist observation data aims to analyze the pedagogical ability of teachers in teaching English. The data from the interview is to find out the competence of the teacher in teaching.Based on the research findings, it shows that the two teachers at SMK NEGERI 4 GOWA still do not meet all the indicators contained in the seven aspects of teacher pedagogical competence.